Examining differences in needs support, satisfaction, and developmental outcomes across competitive and recreational youth sport. - Shaikh, Majidullah; Bean, Corliss; Forneris, Tanya (Université d'Ottawa | University of Ottawa, 2016)
Sport provides an important context for the promotion of positive youth development through engagement in developmentally-appropriate activities and supportive youth-adult relationships. Within sport, both the support of basic psychological needs (i.e. autonomy, competence, and relatedness) and the satisfaction of those needs have been found to aid in positive psychological development. According to Holt and Jones (2008), little research exists that examines youth development outcomes across competitive and recreational sport contexts. Furthermore, to our knowledge, no research has examined differences of basic needs support and satisfaction across these two contexts. Such research would be beneficial for researchers and practitioners to better understand how to structure these types of youth sport. Therefore, the purpose of this study was to examine differences across competitive and recreational youth sport programs on basic needs support, basic needs satisfaction, and PYD outcomes. Youth participants (ages 10-17) completed self-report measures related to the outlined study variables. Results indicated that significant differences existed in which youth involved in recreational programs had higher perceived levels of basic needs support and needs satisfaction than youth involved in competitive programs. In contrast, youth involved in competitive programs perceived their development of some youth development outcomes as greater than those involved in recreational programs. Practical implications and areas for future research are discussed.
Keywords: basic psychological needs; life skills; positive youth development